Energy Efficiency of Low Quality Built Heritage: Methodological Reflections on Achieving the NZEB through a Case Study in the City of L’Aquila - Ieie, Elisa (Journal of Technology Innovations in Renewable Energy, 2018)
About the building heritage and, in particular, about the widespread heritage without historical or architectural quality, it currently opens a challenge in perpetual evolution. This is the integration of innovative technological solutions for building regeneration, which can help a qualitative improvement of the living spaces and the reduction of energy consumptions. Context factors, the intensity of precipitation, the different types of soil, and the amount of solar irradiation or wind speed are doubtless the main causes of the degradation of the existing buildings. On another way, through the control of climatic and biophysical parameters, the focus on the properties of materials and a careful design process, these variables can increase the use of renewable energy sources, becoming environmental resources to reduce energy consumption, to provide comfortable living spaces and aiming the realization of a Near Zero Energy Building. The paper proposes a reflection on the main methodological issues emerged in the hypothesis of intervention experimented on a case study in the city of L’Aquila. The building, located near the historical center of the city, is in direct relation with important pre-existences such as the Forte Spagnolo and the San Salvatore hospital. It is an example of possible regeneration of low quality building in which the additional use of new functional spaces can increase not only energy performances, but also an increase of architectural value of the building.